Effect of working orientations, mass flow rates, and flow directions on thermal performance of annular thermosyphon - Niti Kammuang-Lue (2018)
© 2017 IEEE. Annular thermosyphon or ATS was made from three concentric tubes with difference in diameter. An annular passage lying between an inner tube and a middle tube was evacuated and filled in with working fluid; therefore, a function of this annular passage was identical to that of the passage inside of ordinary thermosyphons. In order to assess possibility to apply the ATS on practical heat transferring applications, this study of which the objective is to experimentally investigate effect of working orientations, mass flow rates of heating and cooling mediums, and flow directions on thermal performance of the ATS has been completely conducted. Distilled water was chosen as the working fluid with tilling ratio of 50% by volume. Heating medium flew in the inner tube while cooling medium flew in a passage lying between the middle and outer tubes. A flow direction of the heating and cooling mediums could be changed between parallel and counter flow by swapping locations of an end of rubber hoses connecting with a hot bath. Working orientation could be adjusted by tilting a test rig where the ATS was secured on. Mass flow rate of the heating and cooling mediums could be individually varied. It was found that when working orientation decreased, or the mass flow rate of the heating medium or the cooling medium increased, or the flow direction changed from counter flow to parallel flow, the heat transfer rate, in turn, the thermal performance increased. In addition, it could be seen that the ATS was more suitable for heat releasing applications than the ordinary thermosyphons when the ATS was restricted to be installed in the horizontal orientation.